Note on a Celtic Cross-Slab and Two Fragments recently found at St Andrews (Proceedings of the Society of Antiquaries of Scotland, 1913)
A complete recumbent slab with a cross upon it was discovered at the cathedral. It shows no trace of decoration, but there is a semicircular cusp in each of the four angles. For the size of the cross the limbs are very broad. There is no ornamentation of any kind either on the reverse or sides. One corner had been broken off, but is now attached again by copper dowels. The slab had apparently been utilised by the builders of the chancel of the church in the thirteenth century. The lower part of a cross-slab close to the Whyte Melville tomb had been utilised by the builders of the wall in the first quarter of the sixteenth century. The shaft of the cross is plain on the obverse and reverse save for the narrow border lines, but on both there is a rich panel on either side of the shaft. A fragment found in the enclosing wall of the infant school had been part of a Celtic cross slab, having sculptured panels both on the obverse and reverse, but on neither is a complete panel left. One has had an effective angular fret pattern, the other an interlaced pattern, which is much wasted.